RETRACTED: Bamboo cellulose based single cell protein and nanocellulose by dilute sulfuric acid hydrolysis and fermentation - Ngoc Ho Khac; Rakhmatullina A.P.; Dien Le Quang; Chung Nguyen Hoang; Dung Ha Thi; Trang Tran Y. Doan (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001